Transparent and High Refractive Index Thermoplastic Polymer Glasses Using Evaporative Ligand Exchange of Hybrid Particle Fillers - Wang, Zongyu; Lu, Zhao; Mahoney, Clare; Yan, Jiajun; Ferebee, Rachel; Luo, Danli; Matyjaszewski, Krzysztof; Bockstaller, Michael R (ACS applied materials & interfaces, 2017)
Development of high refractive index glasses on the basis of commodity polymer thermoplastics presents an important requisite to further advancement of technologies ranging from energy efficient lighting to cost efficient photonics. This contribution presents a novel particle dispersion strategy that enables uniform dispersion of zinc oxide (ZnO) particles in a poly(methyl methacrylate) (PMMA) matrix to facilitate hybrid glasses with inorganic content exceeding 25% by weight, optical transparency in excess of 0.8/mm, and a refractive index greater than 1.64 in the visible wavelength range. The method is based on the application of evaporative ligand exchange to synthesize poly(styrene-r-acrylonitrile) (PSAN)-tethered zinc oxide (ZnO) particle fillers. Favorable filler–matrix interactions are shown to enable the synthesis of isomorphous blends with high molecular PMMA that exhibit improved thermomechanical stability compared to that of the pristine PMMA matrix. The concurrent realization of high refractive index and optical transparency in polymer glasses by modification of a thermoplastic commodity polymer could present a viable alternative to expensive specialty polymers in applications where high costs or demands for thermomechanical stability and/or UV resistance prohibit the application of specialty polymer solutions.